Sikap Remaja Putri dalam Menghadapi Dismenorhoe di SMP Negeri 1 Jenggawah Kecamatan Jenggawah Kabupaten Jember - Surya Dewi Puspita (Universitas Islam Jember, 2018)
Dismenorhoe is derived from abdominal pain and uterine cramping occurs during menstruation. Dismenorhoe is due to elevated levels of prostaglandins in the body, differences in the female reproductive anatomy, accompanied by nausea, dizziness, fainting, anxiety, fatigue, bloating. The purpose of this study was to determine the attitude of the Young Women in Facing Dismenorhoe in SMP Negeri 1 Jenggawah District of Jember Jenggawah This study used a descriptive research design. The sample in this study were 92 respondents from a population of 120 respondents. The sampling technique is simple random sampling with inclusion and exclusion criteria that have been set. The data collection menggunakann measuring instrument questionnaire obtained primary data by calculating a Score T, if the Score T> mdT rated positive attitude (favorable) and the Score T <mdT rated negative attitudes (unfavorable) which means mdT is the average number of scores T, so mdT Score affects T to assess the attitudes. From the results, most of the young women had a positive attitude as much as 62 respondents (67.39%) and only 30 respondents (32.61%) have a negative attitude. Of young women who have experienced dismenorhoe there are 43 respondents (46.74%) have a positive attitude and 9 respondents (9.78%) have a negative attitude. While the young women who have never experienced dismenorhoe as many as 19 respondents (20.65%) have a positive attitude and who have a negative attitude as much as 30 respondents (32.61%). Most teenage daughter 16 years old. Can be concluded that the factor of age, experience, and knowledge of dismenorhoe and management. So, should the young women when dismenorhoe expected to actively seek information and knowledge about good dismenorhoe of media information and consultation with medical experts. This effort is expected to be more effective in preventing chronic dismenorhoe.